Appointing an architectural coordinator to fulfill the obligations under conditions of contract sub clause 8.1 & 15.1 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding appointing an architectural coordinator to fulfill the obligations under conditions of contract sub clause 8.1 & 15.1 of BRAC University new campus project.